2010
DOI: 10.1007/s10586-010-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing parallelism in multicore clusters with the All-Pairs, Wavefront, and Makeflow abstractions

Abstract: Both distributed systems and multicore systems are difficult programming environments. Although the expert programmer may be able to carefully tune these systems to achieve high performance, the non-expert may struggle. We argue that high level abstractions are an effective way of making parallel computing accessible to the non-expert. An abstraction is a regularly structured framework into which a user may plug in simple sequential programs to create very large parallel programs. By virtue of a regular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 32 publications
(35 reference statements)
0
52
0
Order By: Relevance
“…Given that the abstractions Weaver provides related well to those in PEMer (Figure 1), we found it relatively easy to refactor them into a Makeflow [12]. A sample of the code to do this is given in Table 1.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the abstractions Weaver provides related well to those in PEMer (Figure 1), we found it relatively easy to refactor them into a Makeflow [12]. A sample of the code to do this is given in Table 1.…”
Section: Methods and Datamentioning
confidence: 99%
“…Frameworks such as our Makeflow engine [12] provide a straightforward route for software with clear data dependencies and simple serial execution. Because a single bioinformatics Makeflow can be thousands of lines long, we have shown that creating scripts and higher level programs is the key for successful and practical parallelization.…”
Section: Introductionmentioning
confidence: 99%
“…Reuse of components allows developers to use knowledge of their properties to predict the new system properties [12]. (3) Workflow and data flow patterns have been widely studied [11,18]. More advanced data flow abstractions such as MapReduce, or Bulk Synchronous parallel (BSP) constitute the essence of parallel programming frameworks such as Hadoop and Hama.…”
Section: Specification Language For Basic and Advanced Data Flow Applmentioning
confidence: 99%
“…To illustrate a more complex specification with Langliers we present the specification of an operational model for Matrix-Vector Multiplication in streaming based on the wavefront abstraction [18]. The wavefront abstraction is a paradigmatic regularly structured framework that allow developer to focus on simple sequential programs to create very large parallel programs.…”
Section: Langliers Specification Of a Cloud Based Operational Model Omentioning
confidence: 99%
See 1 more Smart Citation